2003
DOI: 10.1002/ca.10172
|View full text |Cite
|
Sign up to set email alerts
|

Branches of the splenic artery and splenic arterial segments

Abstract: In 200 adult autopsy specimens, the arterial supply to the pancreas and spleen was studied radiologically and by manual dissection. The splenic artery divided into two or three lobar arteries, which supplied its corresponding lobe; each lobar artery subsequently divided into two to four lobular branches. Six to twelve lobular branches were observed entering the splenic substance at the hilum. Lobar arteries did not anastomose with each other, hence, the lobes of the spleen are also termed segments. The lobules… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
16
2

Year Published

2008
2008
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(31 citation statements)
references
References 9 publications
2
16
2
Order By: Relevance
“…In the study conducted by Sahni et al. [9] , in 102 of 200 specimens (51%), the superior polar arose from the SA just distal to the origin of the posterior gastric artery and about 4-5 cm proximal to the hilum of the spleen. In 3 of 200 specimens (1.5%), it arose as a branch of the posterior gastric artery.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…In the study conducted by Sahni et al. [9] , in 102 of 200 specimens (51%), the superior polar arose from the SA just distal to the origin of the posterior gastric artery and about 4-5 cm proximal to the hilum of the spleen. In 3 of 200 specimens (1.5%), it arose as a branch of the posterior gastric artery.…”
Section: Discussionmentioning
confidence: 98%
“…A study on this subject reported that, in the majority of cases, it arises from the celiac trunk (90.6%). Rarely, it has origin from the abdominal aorta (8.1%) and from other sites such as the common hepatic artery, left gastric artery, or superior mesenteric artery [8] , [9] . In a few cases, the spleen is supplied by accessory SAs with cases reported originating from the left gastroepiploic artery, left gastric artery, or polar arteries arising primarily from the SA [4] , [10] , [11] .…”
Section: Discussionmentioning
confidence: 99%
“…Tortuosity mainly affects the pancreatic and prepancreatic segments of the splenic artery. Daisy Sahni et al [30] found the splenic artery was tortuous only in 10% of adults. In the present case, splenic artery also gave an additional branch to distal third of transverse colon.…”
Section: Discussionmentioning
confidence: 99%
“…The study of splenic artery anatomy has been complicated by the potential effect of aging on splenic artery tortuosity, as well as the effect of using different methodologies for characterizing the arterial anatomy [15]. An example of this is the assessment of proximity of the splenic artery to the pancreas where gross anatomic and radiographic studies have demonstrated different results [4,11,19]. In an autopsy series, Pandey et al reported that the splenic artery was within the substance of the pancreas in 23.1% cases while in a cohort of patients studied by cross-sectional imaging Zhu and colleagues reported this relationship in 63.3% of cases.…”
Section: Introductionmentioning
confidence: 99%
“…This increased separation may allow a safer approach for device implantation on the splenic artery, lymphadenectomy, or to select cases for vessel sparing distal pancreatectomy. Our understanding of this important anatomic detail is; however, largely derived from cadaveric studies, where degradation and formalin fixation may result in altered vascular and pancreatic anatomy [4,15,18]. Furthermore, it is not systematically described in literature how splenic artery diameters vary between splenic origin and branching the splenic hilum, which can impact design of neuromodulatory devices.…”
Section: Introductionmentioning
confidence: 99%